PENGARUH PEMBELAJARAN BERBASIS VISUAL TERHADAP HASIL BELAJAR PADA MATERI LINGKARAN - Rahman, Antoni; Sahdia, Rahmi Nur; Ekaputri, Yanti Nazmai; Mayeni, Riska; Sefrinal, Sefrinal (STKIP Pesisir Selatan, 2025)
Abstract mathematical concepts, such as the elements of a circle, often pose challenges for students in achieving deep understanding. This study aimed to examine the effect of implementing visual-based learning on students’ learning outcomes in circle material. The research employed a quasi-experimental design with a Pretest-Posttest Control Group Design, involving a population of 63 eighth-grade students at UPT SMPN 3 Ranah Pesisir, with a sample of 42 students divided into experimental and control classes. Data were collected using multiple-choice tests and analyzed with an independent two-sample t-test after confirming data normality and homogeneity. The results indicated a significant difference between the learning outcomes of students who received visual-based learning and those who received conventional instruction, demonstrating that visual-based learning effectively enhances students’ understanding of abstract circle concepts. These findings provide practical implications for teachers in designing more effective, visually-oriented instructional strategies and contribute theoretically by reinforcing evidence that visualization improves the quality of mathematics learning for materials that require concrete and systematic representation.